Efeitos adversos de lixiviados de bitucas e filtros de cigarros no crescimento de uma macrófita flutuante - Yoshida, Luana Lume (Universidade Federal de São Carlos, 2024)
Annually, trillions of cigarette butts are inappropriately discarded in public areas, and through runoff water, they can be inserted into aquatic ecosystems and interact with biota. In this context, the objective of this research was to evaluate the interference of leachates from smoked and unsmoked cigarette butts and filters on the growth of the macrophyte Salvinia auriculata. Nine treatments were performed: (i) control (CT); and leachates from (i) smoked cigarette butts (SB); (ii) unsmoked cigarette butts (USB); (iii) smoked cigarette filters (SF); and (iv) unsmoked cigarette filters (USF), all in four concentrations: 1.0; 1.75; 2.5, and 5.0 butts/filters per liter. Fifty ramets (with two initial leaves each) of the macrophyte were used for each concentration. Through analysis with the Image J software, growth was monitored for nine weeks of weekly photographic records of the macrophytes leaf areas. The growth coefficient (μ) was obtained by adjusting the leaf areas to the logistic model. The CT presented the largest accumulated growth area (12.66 cm² d-1) and the highest growth coefficient value (0.28 d-1). In leachate, the minimum values for the growth area were 9.60 cm² d-1 (SB; p = 0.001), 9.13 cm² d-1 (USF; p = 1.53 x 10-5), 4.03 cm² d-1 (SF; p = 1.29 x 10-5) and 3.59 cm² d-1 (USB; p = 1.51 x 10-6); and for growth velocity they were 0.04 d-1 (SB, SF and USF) and 0.08 d-1 (USB). Thus, the doubling time of S. auriculata increased in contact with cigarette butts and filters. The interference with growth may have derived from the reduction of photosynthetic pigments in the macrophytes, which, in the CT, had a chlorophyll-a content of 0.098 mg DM, chlorophyll-b of 0.047 mg DM and carotenoids of 15.77 mg DM. Although not all leachate concentrations significantly reduced pigments, chlorophyll-a was reduced by up to 0.046 mg DM (SB; p = 0.002), 0.045 mg DM (USB; p = 4.47 x 10-4) and 0.028 mg DM (SF; p = 0.001). Chlorophyll-b was decreased by up to 0.019 mg DM (SB; p = 0.026), 0.016 mg DM (USB; p = 0.006), and 0.013 mg DM (SF; p = 0.011), and carotenoids were reduced by up to 5.54 mg DM (USB; p = 0.009), and 3.87 mg DM (SF; p = 0.001). In addition to reducing pigments, the more acidic leachate with greater electrical conductivity may have contributed to the reduction in macrophyte growth. Among the four types of leachate, the SF derivative showed greater toxicity potential compared to the leachate derived from cigarette butts. The presence of cigarette butts and filters in aquatic ecosystems reduces the growth of S. auriculata, both in the leaf area and in its speed, interfering with its ecological function as a primary producer in the aquatic food chain.
Adverse effects of leachates from cigarette butts and filters on the growth of a floating macrophyte
Keywords: Ecotoxicidade; Coeficiente de crescimento; Área foliar; Salvinia auriculata; Modelagem matemática; Bitucas de cigarro; Ecotoxicity; Growth coefficient; Leaf area; Salvinia auriculata; Mathematical modeling; Cigarette butts; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA